Interactions Between Phenolic Acids and Microorganisms in Rhizospheric Soil From Continuous Cropping of Panax notoginseng - Bao, Limei; Liu, Yuyan; Ding, Yafang; Shang, Junjie; Wei, Yunlin; Tan, Yong; Zi, Futing (Frontiers in Microbiology, 2022)
Large-scale intensive cultivation has made continuous cropping soil sickness more serious for Panax notoginseng in Yunnan. Autotoxic substances can promote the occurrence of continuous cropping soil sickness. Phenolic acids exert a strong autotoxic effect on P. notoginseng. Based on UPLC-MS/MS, the levels of six phenolic acids with the strongest autotoxicity of P. notoginseng rhizospheric soil were tested. Based on Illumina MiSeq high-throughput sequencing technology, the variation in the microbial diversity in the rhizospheric soil was used as an index to explore the interactions between phenolic acids and the soil microorganisms of the P. notoginseng rhizosphere. (1) Continuous P. notoginseng cropping significantly changed the microbial community structure. Continuous cropping increased bacterial Chao1 index and Shannon index and decreased fungal Shannon index. After P. notoginseng disease, bacterial Shannon index reduced and fungal Chao1 index decreased. (2) Phenolic acid significantly changed the bacterial community structure. VA significantly reduced the bacterial Shannon index. Exogenous p-HA, FA, SA and VA significantly increased the fungal Chao1 index and p-HA showed the most significant effect. Para-HA affected bacterial specificity, and VA affected fungal specificity. (3) VA was positively correlated with most fungi and bacteria. Para-HA was positively correlated with Lelliottia and Flavobacterium. Para-HA was also positively correlated with plant pathogens (Fusarium and Ilyonectria). Para-HA and VA were able to promote the growth of primary pathogenic bacteria. Thus, p-HA and VA are the main phenolic acid-autotoxin substances in P. notoginseng under continuous cropping. (4) A correlation analysis of soil environmental factors associated with fungal and bacterial communities showed that AK, TN, OM and HN were most strongly correlated with soil microorganisms. (5) The microorganisms in the rhizosphere of 3-year-old soil planted with P. notoginseng exhibited obvious effects on the degradation of the four phenolic acids. The effect of soil microorganisms on phenolic acids was first-order kinetic degradation with a high degradation rate and a half-life of less than 4.5 h. The results showed that phenolic acids could promote the growth of pathogenic bacteria. And the interaction between rhizospheric soil microorganisms and phenolic acids was the main cause of the disturbance of P. notoginseng rhizosphere microflora.